PENYULUHAN TEKNIK RECORDING DAN PENCEGAHAN PENYAKIT MASTITIS PADA PETERNAK KAMBING PERAH DI KABUPATEN KAMPAR PROVINSI RIAU - Zumarni; Rahmi Febriyanti; Jully Handoko; Sadarman; Muhamad Rodiallah; Yendraliza; Khairuddin; Umar Faruq; Rahmad Yusuf; Fitra, Deni (LPPM ITB AAS Indonesia Surakarta, 2025)
Abstract The implementation of effective recording techniques allows farmers to monitor livestock health more efficiently, identify health issues more quickly, and reduce the incidence of mastitis, which in turn lowers treatment costs and improves the quality of products such as goat milk. However, goat farmers in Kampar Regency, Riau, have not yet adopted good recording techniques. At Fathur Farm, a goat dairy farm, a training session on recording techniques and mastitis prevention was conducted for goat farmers. The methods used in this activity included training and outreach, discussions, and an evaluation at the end. This activity, carried out by lecturers and students from the Animal Science Program at UIN Sultan Syarif Kasim Riau, provided valuable skills in recording techniques and increased farmers' awareness of mastitis prevention, enabling them to apply these practices in their daily routines.